Expression Elements Derived From Plant Sequences Provide Effective Gene Expression Regulation and New Opportunities for Plant Biotechnology Traits - To, Jennifer P. C.; Davis, Ian W.; Marengo, Matthew S.; Shariff, Aabid; Baublite, Catherine; Decker, Keith; Galvão, Rafaelo M.; Gao, Zhihuan; Haragutchi, Olivia; Jung, Jee W.; Li, Hong; O'Brien, Brent; et al. (Frontiers in Plant Science, 2021)
Plant biotechnology traits provide a means to increase crop yields, manage weeds and pests, and sustainably contribute to addressing the needs of a growing population. One of the key challenges in developing new traits for plant biotechnology is the availability of expression elements for efficacious and predictable transgene regulation. Recent advances in genomics, transcriptomics, and computational tools have enabled the generation of new expression elements in a variety of model organisms. In this study, new expression element sequences were computationally generated for use in crops, starting from native Arabidopsis and maize sequences. These elements include promoters, 5’ UTRs, introns, and 3’ UTRs. The expression elements were demonstrated to drive effective transgene expression in stably transformed soybean plants across multiple tissues-types and developmental stages. The expressed transcripts were characterized to demonstrate molecular function of these expression elements. The data show that: the promoters precisely initiate transcripts; the introns are effectively spliced; and the 3’ UTRs enable predictable processing of transcript 3’ ends. Overall our results indicate that these new expression elements can recapitulate key functional properties of natural sequences and provide opportunities for optimizing the expression of genes in future plant biotechnology traits.